2019
DOI: 10.1111/ajt.15523
|View full text |Cite
|
Sign up to set email alerts
|

Vendor-specific microbiome controls both acute and chronic murine lung allograft rejection by altering CD4+Foxp3+ regulatory T cell levels

Abstract: Despite standardized postoperative care, some lung transplant patients suffer multiple episodes of acute and chronic rejection while others avoid graft problems for reasons that are poorly understood. Using an established model of C57BL/10 to C57BL/6 minor antigen mismatched single lung transplantation, we now demonstrate that the recipient microbiota contributes to variability in the alloimmune response. Specifically, mice from the Envigo facility in Frederick, Maryland contain nearly double the number of CD4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 39 publications
2
20
2
Order By: Relevance
“…21,22,25,[34][35][36][37][38] We have found that fibrosis diminishes over time with surgical experience, and currently we observe minimal fibrosis in allografts not subjected to IRI, in contrast to our earlier data. Allograft fibrosis in the B10→B6 LT model is highly variable among different surgeons and research groups, whereas AR is mild but reproducible.…”
Section: Cold and Warm Ischemic Preservation Augment Allograft Fibrcontrasting
confidence: 93%
See 2 more Smart Citations
“…21,22,25,[34][35][36][37][38] We have found that fibrosis diminishes over time with surgical experience, and currently we observe minimal fibrosis in allografts not subjected to IRI, in contrast to our earlier data. Allograft fibrosis in the B10→B6 LT model is highly variable among different surgeons and research groups, whereas AR is mild but reproducible.…”
Section: Cold and Warm Ischemic Preservation Augment Allograft Fibrcontrasting
confidence: 93%
“…Allograft fibrosis in the B10→B6 LT model is highly variable among different surgeons and research groups, whereas AR is mild but reproducible. 21,22,25,[34][35][36][37][38] We have found that fibrosis diminishes over time with surgical experience, and currently we observe minimal fibrosis in allografts not subjected to IRI, in contrast to our earlier data. 20 We therefore hypothesized that the limited fibrotic WIT nor 30 minutes CIT plus 60 minutes WIT caused CR (not shown).…”
Section: Cold and Warm Ischemic Preservation Augment Allograft Fibrcontrasting
confidence: 93%
See 1 more Smart Citation
“…[20][21][22] Direct T cell contact with antigen-presenting cells also appears to be required for peripheral conversion of naive T cells into Tregs, as this process requires engagement of T cell receptors and costimulatory molecules. 26 23,24 For example, we have shown that selective elimination of MHCII expression on non-hematopoietic cells in the lung resulted in reduced local generation of Tregs, which was associated with enhanced inflammation.…”
Section: De Velopment Of Reg Ul Atory T Cell Smentioning
confidence: 99%
“…To this end, we have recently demonstrated that recipient microbiota has a significant impact on the pulmonary and systemic levels of Tregs following lung transplantation, suggesting a potential link between dysbiosis and an increased risk of acute and chronic rejection. 26…”
Section: De Velopment Of Reg Ul Atory T Cell Smentioning
confidence: 99%